2020
DOI: 10.1002/cmdc.202000040
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and SAR of Tetracyclic Inhibitors of Protein Kinase CK2 Derived from Furocarbazole W16

Abstract: The serine/threonine kinase CK2 modulates the activity of more than 300 proteins and thus plays a crucial role in various physiological and pathophysiological processes including neurodegenerative disorders of the central nervous system and cancer. The enzymatic activity of CK2 is controlled by the equilibrium between the heterotetrameric holoenzyme CK2α 2 β 2 and its monomeric subunits CK2α and CK2β. A series of) was prepared in an one-pot, three-component Levy reaction. The stereochemistry of the tetracyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“… 33 For kinase reaction, kinase buffer (50 mM Tris-HCl [pH 7.5], 100 mM NaCl, 10 mM MgCl 2 ) containing 70 nM CK2α and 140 nM CK2β (wild type and both mutants NP_001311.3; p.Asp32His and NP_001311.3; p.Asp32Asn) was pre-incubated for 10 min at 37 °C. After adding pre-incubated assay buffer (25 mM Tris-HCl [pH 8.5], 150 mM NaCl, 5 mM MgCl 2 , 190 μM substrate peptide RRRDDDSDDD 34 [GenicBio, Shanghai, China] and 60 μM ATP), the samples were incubated at 37 °C for 1, 2, 3, 4, and 5 min. The reaction was stopped by decreasing the temperature to 4°C and addition of 5 μL EDTA (0.5 M).…”
Section: Methodsmentioning
confidence: 99%
“… 33 For kinase reaction, kinase buffer (50 mM Tris-HCl [pH 7.5], 100 mM NaCl, 10 mM MgCl 2 ) containing 70 nM CK2α and 140 nM CK2β (wild type and both mutants NP_001311.3; p.Asp32His and NP_001311.3; p.Asp32Asn) was pre-incubated for 10 min at 37 °C. After adding pre-incubated assay buffer (25 mM Tris-HCl [pH 8.5], 150 mM NaCl, 5 mM MgCl 2 , 190 μM substrate peptide RRRDDDSDDD 34 [GenicBio, Shanghai, China] and 60 μM ATP), the samples were incubated at 37 °C for 1, 2, 3, 4, and 5 min. The reaction was stopped by decreasing the temperature to 4°C and addition of 5 μL EDTA (0.5 M).…”
Section: Methodsmentioning
confidence: 99%
“…86 Recently, Kröger et al found that the enantiomer of W16 was six times more potent than its analogue (K i = 4.9 μM vs. 31 μM respectively). 87 They also replaced the labile anhydride group of W16 with a more stable imide and N-methylimide, increasing stability without the loss of binding affinity (K i = 3.6 μM vs. 2.8 μM respectively). However, the increased inhibition of the PPI did not result in a greater biological effect as the new analogues of W16 were not seen to inhibit CK2.…”
Section: Reviewmentioning
confidence: 99%
“…This clearly highlights that perturbation to the equilibrium of the CK2 holoenzyme complex formation does not necessarily lead to enzyme inhibition. 87 Due to the large aromatic structures of the podophyllotoxin indolo-analogues, the compounds suffer from poor solubility making the likelihood of developing therapeutics derived from W16 low. 86,87 A high-concentration X-ray crystallography fragment screen identified 1 (in Brear et al) binding at both the CK2α/β interface and in the ATP-pocket of CK2 with a weak IC 50 (900 μM).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations